Women`s football: don`t judge me, support me! evidence from young generations - Giachino, C.; Valenti, M.; Bonadonna, A.; Bollani, L. (Soccer & Society, 2024)
The aim of the paper is to understand how young generations consider women playing football since women`s football still struggles to reach and gain consistent fan followings. Women`s football stakeholders are in need to inspire viewers and spectators in order to improve the visibility and commercialization of the game. A survey was administered and distributed to 2,298 participants belonging to both Millennials and Generation Z cohorts. Predictors of interest in women`s football were tested based on such information and a cluster analysis was conducted to group participants based on common characteristics and views on women`s football. Results show that there is a connection among past or current sport playing experience, general interest in sports and positive attitude towards women in football. Generation Z and Young Millennials are more favourable towards women in football and find it normal. However, there are still some people who disapprove this sport.